A "Gold‐centric" implementation of open access: Hybrid journals, the "Total cost of publication, " and policy development in the UK and beyond. (27th February 2017) - Pinfield, Stephen; Salter, Jennifer; Bath, Peter A.
Abstract : This paper reports analysis of data from higher education institutions in the UK on their experience of the open‐access (OA) publishing market working within a policy environment favoring "Gold" OA (OA publishing in journals). It models the "total cost of publication"—comprising costs of journal subscriptions, OA article‐processing charges (APCs), and new administrative costs—for a sample of 24 institutions. APCs are shown to constitute 12% of the "total cost of publication, " APC administration, 1%, and subscriptions, 87% (for a sample of seven publishers). APC expenditure in institutions rose between 2012 and 2014 at the same time as rising subscription costs. There was disproportionately high take up of Gold options for Health and Life Sciences articles. APC prices paid varied widely, with a mean APC of £1, 586 in 2014. "Hybrid" options (subscription journals also offering OA for individual articles on payment of an APC) were considerably more expensive than fully OA titles, but the data indicate a correlation between APC price and journal quality (as reflected in the citation rates of journals). The policy implications of these developments are explored, particularly in relation to hybrid OA and potential of offsetting subscription and APC costs.